Benchmarking of hygiene and sanitation performance of public food markets in Vientiane, Lao PDR - Souphonesay Lorphengsy; Perera, L.A.S. Ranjith; Vilas Nitivattananon; Kusakabe, Kyoko; Canada (CIDA) (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
There happens to be a lack of understanding as to how hygiene and sanitation standards of public food markets can contribute to the quality of life. Appropriate benchmarking of markets can lead to improve their performances. This research was carried out to compare the prevailing hygiene and sanitation performance of a public food market in Vientiane with a model healthy market. The Thong Khan Kham Market (TKKM) in Vientiane was selected for the study and was compared with the Ying Charoen Market (YCM) in Bangkok. A sample survey was conducted among 76 vendors and 50 customers in TKKM to review the performance of hygiene and sanitation. In addition, interviews with officials and field observations were carried out at both TKKM and YCM. The study shows that overall situation of hygiene and sanitation remains to be major issues of TKKM in comparison to YCM. Since most of the vendors are women, they were found to be worst affected due to inadequate hygiene and sanitation level in TKKM. Disorganized management, poor governance and absence of market standards in TKKM were identified as the reasons for the shortcomings. Based on the benchmarking experience, recommendations are made to improve the condition of the TKKM
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Environmental Management
Thesis (M.Sc.) - Asian Institute of Technology, 2009
Keywords: Markets -- Sanitation -- Laos -- Vientiane